MHC class I surface expression in embryo-derived cell lines inducible with peptide or interferon. - Bikoff, E; Jaffe, L; Ribaudo, R; Otten, G; Germain, R; Robertson, E (1991)
It has long been recognized that the absence of expression of products of the major histocompatibility complex (MHC) during early development might allow the fetus to escape recognition by maternal lymphocytes. In addition to the MHC class I heavy chain and beta 2-microglobulin, antigenic peptide is an essential structural component of the class I molecule. Indeed, there is evidence that MHC-linked genes encoding peptide transporter molecules and possibly components of a proteolytic complex are necessary for MHC class I assembly and stability at the cell surface. Here we demonstrate that embryonic cells in general show a defect in MHC class I assembly. Surface expression was rescued in the presence of an appropriate antigenic peptide, or by treatment with interferon. Consistent with this, HAM1 messenger RNA was not constitutively expressed, but was inducible by interferon, and during differentiation in vitro. Thus, tolerance of the fetal allograft may in part be controlled at the level of peptide-dependent MHC class I assembly.